2022
DOI: 10.7554/elife.72251
|View full text |Cite
|
Sign up to set email alerts
|

The Cl--channel TMEM16A is involved in the generation of cochlear Ca2+ waves and promotes the refinement of auditory brainstem networks in mice

Abstract: Before hearing onset (postnatal day 12 in mice), inner hair cells (IHC) spontaneously fire action potentials thereby driving pre-sensory activity in the ascending auditory pathway. The rate of IHC action potential bursts is modulated by inner supporting cells (ISC) of Kölliker's organ through the activity of the Ca2+ activated Cl- channel TMEM16A (ANO1). Here we show that conditional deletion of Ano1 (Tmem16a) in mice disrupts Ca2+ waves within Kölliker's organ, reduces the burst firing activity and the freque… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 80 publications
(158 reference statements)
1
14
0
Order By: Relevance
“…Similarly, SGNs in Tmem16a KO mice exhibit altered firing patterns, including near elimination of long burst events and prolongation of inter-spike intervals ( Wang et al, 2015 ). A recent report suggested that TMEM16A enhances ATP release through positive feedback mechanisms in the cochlea ( Maul et al, 2022 ); however, we observed no significant change in the frequency, amplitude, duration, or area of calcium transients in ISCs of Tmem16a cKO mice ( Figures S3A – S3D ; Video S1 ), in accordance with prior observations ( Wang et al, 2015 ). These results indicate that TMEM16A is required to induce periodic, coordinated activation of IHCs throughout the postnatal pre-hearing period, providing a means to selectively disrupt spontaneous activity in the auditory system during this crucial period of development.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Similarly, SGNs in Tmem16a KO mice exhibit altered firing patterns, including near elimination of long burst events and prolongation of inter-spike intervals ( Wang et al, 2015 ). A recent report suggested that TMEM16A enhances ATP release through positive feedback mechanisms in the cochlea ( Maul et al, 2022 ); however, we observed no significant change in the frequency, amplitude, duration, or area of calcium transients in ISCs of Tmem16a cKO mice ( Figures S3A – S3D ; Video S1 ), in accordance with prior observations ( Wang et al, 2015 ). These results indicate that TMEM16A is required to induce periodic, coordinated activation of IHCs throughout the postnatal pre-hearing period, providing a means to selectively disrupt spontaneous activity in the auditory system during this crucial period of development.…”
Section: Resultssupporting
confidence: 93%
“…A recent study by Maul et al (2022) used a similar approach to explore the role of spontaneous activity in auditory development by targeting TMEM16A. Genetic inactivation of Tmem16a resulted in a dramatic decrease in spontaneous action potential burst frequency and increased inter-spike intervals in the MNTB, similar to the firing patterns observed in SGNs from isolated Tmem16a KO cochleae ( Wang et al, 2015 ), but action potential firing was not eliminated, likely because of tonic IHC depolarization.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations